Influência do índice de massa corporal na evolução da diabetes gestacional - Domingues, Ana Patrícia (2007)
Objective: To evaluate the implications of body mass index (BMI) in pregnancies complicated with gestational diabetes (GD). Study Design: Retrospective assessment of pregnancies complicated with GD managed at our institution from January 2000 to December 2004. Results: Obstetrical complications beyond GD occurred in: group A (BMI 20-24,9) - 23%; group B (BMI 25-29,9) - 18.8% and group C (BMI>30) - 35.3%, including hypertensive disorders in A-1.65%, B-3.76% and C-9.6%. Mean value of HbA1c at third trimester was A-5.05, B-5.25 e C-5.41%. Insulin treatment was needed in A 26.1%, B-41% and C-50.6%, and was started on average at A-32.8, B-30.5 and C-29.3 gestational weeks. Delivery occurred on average at 38 weeks in the three groups, with caesarean rates of A-26.7%, B-33.1% and C-38.5%. Mean birthweight of the newborns was A-3189g, B-3307g and C- 3469g. There were 5 perinatal deaths (A-1, B-2 and C-2). Maternal and neonatal morbidity were not significantly different in the three groups. Conclusions: Obese pregnant women with GD had a higher mean maternal age, higher rates of obstetrical complications (hypertensive in particular), higher levels of HbA1c in the third trimester, needed insulin treatment more frequently and at earlier gestational ages, and their newborns were heavier.